Effective Communication: A Panacea to Jigsaw of Ponzi Scheme and Misrepresentation of Investment in Ekiti State Universities, Nigeria - Asaolu, Adepoju Adeoba (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2026)
Purpose: This study examined the effect of Ponzi scheme-related factors on investors’ behaviour among students of Ekiti State University, Ado-Ekiti and Federal University, Oye-Ekiti. The specific objectives were to examine how the frequency of Ponzi scheme exposure affects students’ perception of investment opportunities, determine the relationship between the level of misrepresentation in investment schemes and students’ investment decision-making, and evaluate how the effectiveness of communication strategies influences students’ awareness and prevention of Ponzi schemesamong university students in Ekiti State, NigeriaMethodology: The study used a survey research design and a structured questionnaire was used to collect primary data for the studywith a total of 394 who were sampled using the Taro Yamane sampling techniquewith proportional distribution across the faculties of the universityResults and Conclusion: Regression analysis was used in the analysis of data. The results indicated that the frequency of encountering Ponzi schemes positively and insignificantly affects students’ perception of investment opportunities. The results further revealed that misrepresentation in investment schemes has a positive and significant effecton students' investment decision-making. Moreover, the study revealed that the communication strategies have a positive and significant relationship with investors in terms of awareness and prevention of Ponzi schemes. Implication of findings: The results indicate that only awareness of Ponzi schemes will not significantly affect the Student perception of investment opportunities , reflecting the fact that awareness alone is not enough.
Keywords: Ponzi Scheme; Misrepresentation; Effective Communication; Investor Behaviour; Financial Literacy